2021
DOI: 10.1186/s12870-021-03066-7
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Seq analysis reveals potential regulators of programmed cell death and leaf remodelling in lace plant (Aponogeton madagascariensis)

Abstract: Background The lace plant (Aponogeton madagascariensis) is an aquatic monocot that develops leaves with uniquely formed perforations through the use of a developmentally regulated process called programmed cell death (PCD). The process of perforation formation in lace plant leaves is subdivided into several developmental stages: pre-perforation, window, perforation formation, perforation expansion and mature. The first three emerging “imperforate leaves” do not form perforations, while all subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 111 publications
1
7
0
Order By: Relevance
“…Both Atg16 mRNA and protein levels were significantly higher in pre-perforation and window stage leaves compared to mature and imperforate leaves. These levels are correlated with early stages of lace plant leaf development when PCD and anthocyanin accumulation is active ( Fig 2A and 2D ) and are also consistent with the RNA-Seq data revealed in Rowarth et al, (2021) [ 46 ]. Pre-perforation and window stage leaves have been shown to up-regulate transcripts encoded for genes involved in autophagy promotion such as Atg16 , Atg18a , and SNF1-related protein kinase KIN10 [ 46 , 55 ] suggesting an increased need for autophagosome formation and cell maintenance during early lace plant developmental PCD.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Both Atg16 mRNA and protein levels were significantly higher in pre-perforation and window stage leaves compared to mature and imperforate leaves. These levels are correlated with early stages of lace plant leaf development when PCD and anthocyanin accumulation is active ( Fig 2A and 2D ) and are also consistent with the RNA-Seq data revealed in Rowarth et al, (2021) [ 46 ]. Pre-perforation and window stage leaves have been shown to up-regulate transcripts encoded for genes involved in autophagy promotion such as Atg16 , Atg18a , and SNF1-related protein kinase KIN10 [ 46 , 55 ] suggesting an increased need for autophagosome formation and cell maintenance during early lace plant developmental PCD.…”
Section: Discussionsupporting
confidence: 90%
“… An unknown induction signal(s) during window leaf development initiates the differentiation of PCD from NPCD cells within the areole, visible by an imbalance between reactive oxygen species (ROS) and anthocyanin [ 16 ]. RNA-Seq analysis has shown that window leaves up-regulate genes such as Atg18a and SNF1RK that promote autophagy [ 46 ]. During window stage of leaf development Atg8 [ 29 ] and Atg16 protein levels are high and can be manipulated by autophagy modulators [this study, 56].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations